Physical activity as an efficient means of non - pharmacological care in oncology - Kapounková, Kateřina; Hrnčiříková, Iva; Svobodová, Zora; Šimonová, Marie; Struhár, Ivan; Halámková, Jana; Burešová, Iva; Hadrabová, Markéta; Janíková, Andrea; Bazalová, Pavlína (Masaryk University Press, 2024)
The publication focuses on methods of physical activity in treatment of cancer. Intended for professional public.
Keywords: terapie cvičením; Motor Activity; onkologie; nádory; rehabilitační a fyzikální medicína; Neoplasms; pohybová aktivita; Exercise Therapy